Teacher training as a means to instil sustainable environmental behaviour among future teachers: a systematic literature review - Abdul Karim, Aini Arifah; Abdullah, Sabrina; Mohd Ayub, Ahmad Fauzi; Sharaai, Amir Hamzah (Human Resource Management Academic Research Society, 2021)
Teachers training is considered part of human resource development and indispensable in the realization of educational goals. Teacher training carries an important role in the human resources development especially in preparing the citizens of the nation into becoming an individual with sustainable behaviours. Much research has been done in studying how teacher training helps in changing their behaviour towards sustainability and love towards the environment. Few systematic reviews have been carried out on the sustainability in the educational sector. Education for sustainable development undeniably establishes the society’s need for some transformation within the education sector; especially in the training of the teachers prior to their pursuit in embarking as real teachers. It is inevitable that teacher education has become a priority for orienteering the teachers in terms of sustainability. The present article aims to analyse the existing literature on pre service teachers’ education towards the impact of change in the behaviour. This review is guided by the PRISMA statement (Preferred Reporting Items for Systematic reviews and Meta-Analyses) review method. A systematic review of the Scopus and Web of Science databases resulted in 19 related studies. Further review of these articles resulted in 4 major themes which are Measurement, Implementation, Factors and Methods/ Teaching Strategies. These 4 themes further produced 15 outcome variables. Several recommendations are highlighted related to use NVivo or Atlas. Ti as an analysis tool and to practice complimentary searching techniques such as citation tracking, reference searching, snowballing and contacting experts.